2013
DOI: 10.1111/j.1365-2826.2012.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Desensitisation of c‐Fos Expression Induced by Repeated Maternal Separation in Pre‐Weaned Mice

Abstract: Early-life stress has long-lasting effects on neuroendocrine and behaviour in adulthood. Maternal separation (MS) is used as a model of early-life stress and daily repeated MS (RMS) for 3 h during the first two postnatal weeks is widely used in rodent studies. However, it is not fully understood whether early-life animals desensitise/habituate to repeated stress. In the present study, we investigated the effects of daily RMS for 3 h and acute/single time MS (SMS) for 3 h on the plasma corticosterone level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 48 publications
4
37
1
Order By: Relevance
“…The present observations suggest that MSSI increases p‐ERK expression in multiple brain regions under conditions of basal or neuropathic pain. In agreement, previous studies demonstrate that maternal separation increase p‐ERK expression in the amygdala (Park et al., ), and that the immediate early gene product and marker of activated neurons c‐fos was increasingly expressed in multiple brain regions following exposure to maternal separation (Horii‐Hayashi et al., ). Hence, early life stress activates neuronal function in multiple brain regions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present observations suggest that MSSI increases p‐ERK expression in multiple brain regions under conditions of basal or neuropathic pain. In agreement, previous studies demonstrate that maternal separation increase p‐ERK expression in the amygdala (Park et al., ), and that the immediate early gene product and marker of activated neurons c‐fos was increasingly expressed in multiple brain regions following exposure to maternal separation (Horii‐Hayashi et al., ). Hence, early life stress activates neuronal function in multiple brain regions.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, mice were stimulated by light touch under non‐anaesthetized conditions, which may have influenced brain p‐ERK expression. Furthermore, maternal separation was previously shown to induce p‐ERK expression in the amygdala, and c‐fos expression in multiple brain regions without light touch stimulation (Horii‐Hayashi et al., ; Park et al., ). Therefore, although brain p‐ERK expression is not correlated with pain sensitivity, neuronal activity in several brain regions is elevated by MSSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even natural variations in the quality or quantity of maternal care can have a long-term impact on offspring brain and behaviour. Human epidemiological and animal experimental studies show that early social experiences influence the functioning of physiological processes even into adulthood (3,(16)(17)(18)(19)(20)(21)(22).…”
Section: Maternal Separation Stress and Reproductive Function: Effectmentioning
confidence: 99%
“…Kasumovic & Brooks, ). However, information on gene expression changes influencing phenotypic development during ontogeny remains scarce (Horii‐Hayashi et al, ; Schmidt et al, ; Vazquez et al, ). Using a time series approach, we showed that in the cichlid fish Neolamprologus pulcher social experience influences whole‐brain gene expression during a stage when these fish have already developed a social behaviour repertoire (see Arnold & Taborsky, ) and are at the verge of becoming brood care helpers (Kasper et al, ).…”
Section: Discussionmentioning
confidence: 99%